2009
DOI: 10.1080/10715760903037673
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic acid modulates thiol antioxidant defences and attenuates exercise-induced oxidative stress in standardbred trotters

Abstract: Several micronutrient supplementation strategies are used to cope with oxidative stress, although their benefits have recently been questioned. The aim of the present study was to examine the effects of DL-alpha-lipoic acid (LA) in response to acute exercise and during recovery in horses. Six standardbred trotters were tested on the treadmill before and after 5-week LA supplementation (25 mg/kg body weight/day). According to electron paramagnetic resonance measurements, strenuous aerobic exercise increased sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
1
20
0
1
Order By: Relevance
“…As a result, GSH oxidation, which is a sensitive marker of oxidative stress, occurs less after exercise in trained individuals. Recently, we observed that in the regularly trained horse, with exercise or during recovery, there were no significant changes in the muscle GSSG-or the GSH-redox ratio, although postexercise free-radical amounts correlated positively with postexercise GSSG concentration (184). This can be explained by the well-known fact that regular exercise training of all types enhances GSH levels by inducing GSH synthesis and also by increasing GSH regeneration from GSSG (361).…”
Section: B Thiols and Redox Signaling In Exercisementioning
confidence: 71%
“…As a result, GSH oxidation, which is a sensitive marker of oxidative stress, occurs less after exercise in trained individuals. Recently, we observed that in the regularly trained horse, with exercise or during recovery, there were no significant changes in the muscle GSSG-or the GSH-redox ratio, although postexercise free-radical amounts correlated positively with postexercise GSSG concentration (184). This can be explained by the well-known fact that regular exercise training of all types enhances GSH levels by inducing GSH synthesis and also by increasing GSH regeneration from GSSG (361).…”
Section: B Thiols and Redox Signaling In Exercisementioning
confidence: 71%
“…58 These findings, plus the beneficial in situ aspects of 2-Me found for aging mice and rats, 23,[38][39][40] raise the question as to why stronger redox-SH molecules have not been more extensively evaluated for therapeutic value. Is the major obstacle curtailing evaluation of the two strongest, 2-Me and dithiothreitol, their potentially lethal manifestations?…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, alterations in redox homeostasis have been reported in mdx mice [an animal model for Duchenne muscular dystrophy, which lacks dystrophin (Radley-Crabb et al, 2011)], C57/BL6J mice (Yokota et al, 2009), BALB/c mice (De la Fuente et al, 1995), Swiss mice (Prigol et al, 2009), Hsd:ICR mice, which had been selected for high wheel-running activity (Vaanholt et al, 2008), and guinea pigs (De la Fuente et al, 1995). Finally, exercise has been reported to induce alterations in redox homeostasis in fish (Aniagu et al, 2006), birds (Costantini et al, 2008;Costantini and Lipp, 2010;Larcombe et al, 2010), dogs (Wyse et al, 2005) and horses (Kinnunen et al, 2009). Based on the above-mentioned analysis, it is evident that exercise-induced changes in redox homeostasis are a ubiquitous fundamental response of most (if not all) animal species, irrespective of definite differences in redox composition across species and between non-human animal models and humans.…”
Section: Acute Exercise Alters Redox Homeostasis Across Strains and Smentioning
confidence: 99%
“…Indeed, several studies have indicated that antioxidant supplementation induces a positive effect (Jakeman and Maxwell, 1993;Shafat et al, 2004), a negative effect (Gomez-Cabrera et al, 2008;Ristow et al, 2009) or no effect (Yfanti et al, 2010;Kyparos et al, 2011;Theodorou et al, 2011) on muscle performance. Likewise, several studies have reported that antioxidant supplementation attenuates oxidative stress (Close et al, 2006;Kinnunen et al, 2009), others have reported that it induces a pro-oxidant effect (McAnulty et al, 2005;Versari et al, 2006) and others have reported that it does not affect redox homeostasis (Rytter et al, 2010;Theodorou et al, 2011). The hormetic concept predicts that the effects of antioxidant supplementation on muscle performance and redox homeostasis are dependent on the antioxidant dose.…”
mentioning
confidence: 99%